IBM DS8880 product guide (Release 8.51) - Dufrasne, Bertrand; Toser, Tamas; Kimmel, Peter; Manthorpe, Stephen (IBM Corporation, International Technical Support Organization, 2019)
This IBM Redbooks® Product Guide gives an overview of the features and functions that are available with the IBM DS8880 models running microcode Release 8.51 (DS8000 License Machine Code 8.8.51.xx.xx). The IBM DS8880 architecture relies on powerful IBM POWER8® processor-based servers that manage the cache to streamline disk input/output (I/O), maximizing performance and throughput. These capabilities are further enhanced with the availability of the second generation of high-performance flash enclosures (HPFE Gen-2). The IBM DS8888, DS8886, and DS8884 models excel at supporting the IBM Z Enterprise server and IBM Power server environments, offering many synergy features.
Date of publication from resource description page. - "Product guide.". - Number on back cover: REDP-5344-03. - Includes bibliographical references. - Online resource; title from cover (Safari, viewed September 26, 2019)
Keywords: Storage area networks (Computer networks); Computer architecture; Client/server computing; Réseaux de stockage (Informatique); Ordinateurs; Architecture; Architecture client-serveur (Informatique)